Feeding Grazing Dairy Cows With Different Energy Sources on Recovery of Human-Edible Nutrients in Milk and Environmental Impact - Batistel, Fernanda; de Souza, Jonas; Vaz Pires, Alexandre; Santos, Flávio Augusto Portela (Frontiers in Sustainable Food Systems, 2021)
The use of grazing systems for milk production is widely used globally because it is a lower-cost feeding system. However, under tropical conditions, the energy content of pastures became is a limitation to improve animal performance and efficiency while reducing the environmental impact. The objective of our study was to evaluate the impact of supplying different dietary sources of energy to lactating dairy cows grazing tropical pastures on the recovery of human-edible (HE) nutrients in milk and the environmental impact. Two experiments were conducted simultaneously. In experiment 1, forty early lactating dairy cows were used in a randomized block design. In experiment 2, four late-lactating rumen-cannulated dairy cows were used in a 4 × 4 Latin Square design. All cows had free access to pasture and treatments were applied individually as a concentrate supplement. Treatments were flint corn grain-processing method either as fine ground (FGC) or steam-flaked (SFC) associated with Ca salts of palm fatty acids supplementation either not supplemented (CON) or supplemented (CSPO). We observed that feeding cows with SFC markedly reduced urinary nitrogen excretion by 43%, and improved milk nitrogen efficiency by 17% when compared with FGC. Additionally, we also observed that feeding supplemental fat improved milk nitrogen efficiency by 17% compared with cows receiving CON diets. A tendency for decreased methane (CH4) per unit of milk (-31%), CH4 per unit of milk energy output (-29%), and CH4 per unit of milk protein output (-31%) was observed when CSPO was fed compared with CON. Additionally, SFC diets increased HE recovery of indispensable amino acids by 7 to 9% when compared with FGC diets, whereas feeding supplemental fat improved HE recovery of indispensable amino acids by 17 to 19% compared with CON. Altogether, this study increased our understanding of how manipulating energy sources in the dairy cow diet under tropical grazing conditions can benefit HE nutrient recovery and reduce nutrient excretion.